2016
DOI: 10.3892/mco.2016.874
|View full text |Cite
|
Sign up to set email alerts
|

Curative resection for leiomyosarcoma of the descending mesocolon with metachronous liver metastasis: A case report and literature review

Abstract: Mesenteric leiomyosarcoma is a rare disease with poor prognosis. Previously, mesenteric leiomyosarcoma was not differentiated from gastrointestinal stromal tumor (GIST), which is the most common mesenchymal tumor of the gastrointestinal tract, and several cases of GIST may have been misclassified as mesenteric leiomyosarcoma. Thus, the actual clinicopathological characteristics of mesenteric leiomyosarcomas remain unclear. We herein describe a case of leiomyosarcoma arising in the descending mesocolon in a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…The median follow-up time for the cases presented (n = 17) was 22.6 months (range: 3-59), and consistent with the findings of Kato et al [5], no patient was reported to survive 59 months ( Table 1) [11].…”
supporting
confidence: 86%
See 3 more Smart Citations
“…The median follow-up time for the cases presented (n = 17) was 22.6 months (range: 3-59), and consistent with the findings of Kato et al [5], no patient was reported to survive 59 months ( Table 1) [11].…”
supporting
confidence: 86%
“…Given that LMSs originate from smooth muscle cells, confirming the diagnosis with IHC is necessary for accurate diagnosis [5]. SMA (n = 17) was positive in 100% of the reported cases.…”
Section: Literature Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five-year survival rate is only 20%–30% and the complete surgical resection will favour the outcome. Case series and literature review by Kato et al in 2016 stated that since 1998, it was 13 cases which have been reported so far by proper immunohistochemistry 13. Kato et al added that the recurrence can occur within 5 years, and periodic monitoring is recommended using imaging modality to monitor the progression following the surgical resection.…”
Section: Discussionmentioning
confidence: 99%